Status Kepesertaan JKN Nonaktif Sebagai Dasar Penolakan Pasien: Analisis Yuridis terhadap Undang-Undang No 17 Tahun 2023 tentang Kesehatan - Emirza Nur Wicaksono; Rosalina Rosalina (Journal of Contemporary Law Studies, 2026)
This research aims to legally analyze whether the inactive status of National Health Insurance (JKN) membership can be used as a basis for refusing patients from the perspective of Law No. 17 of 2023 concerning Health. This issue arises from field practices indicating service restrictions against inactive JKN participants, which potentially contradicts the principles of the right to health and non-discrimination. This study employs a normative legal research method with a statutory and conceptual approach. Primary and secondary legal materials are analyzed systematically through legal interpretation and norm harmonization. The results indicate that the right to health services under Law No. 17 of 2023 is a fundamental right that cannot be restricted by administrative membership status. Inactive JKN status lacks a valid legal basis to serve as a reason for refusing patients, particularly when it hinders the fulfillment of the right to health. Furthermore, the study identifies a vacuum in operational norms and a lack of integrated regulation between the Health Law and technical JKN regulations. This research contributes to the development of health law by strengthening a rights-based approach and offering an ideal legal construction that balances the protection of patient rights with the sustainability of national health financing.